Brazilian Historical Writing in Global Perspective: On the Emergence of the Concept of “Historiography” - Pereira, Mateus Henrique de Faria (History and theory, 2015)
This article assesses the meanings of the term “historiography” in Brazilian historiography from the late nineteenth century to circa 1950, suggesting that its use plays an essential role in the process of the disciplinarization and legitimation of history as a discipline. The global-scale comparison, taking into consideration occurrences of the term in German, Spanish, and French, reveals that use of the term took place simultaneously worldwide. The term “historiography” underwent a significant change globally, having become independent from the modern concept of history, shifting away from the political and social dimensions of the writing of history in the nineteenth century and unfolding into a metacritical concept. Such a process enables historians to technically distinguish at least three semantic modulations of the term: 1. history as a living experience; 2. the writing or narration of history; and 3. the critical study of historical narratives. Based on the Brazilian experience, it is possible to think of the “historiography” category as an index of the transformations of the modern concept of history itself between the 1870s and 1940s, a period of intense modification of the experience and expectations of the writing of professional historical scholarship on a global scale.